Proceedings of the 19th ACM SIGKDD International Conference on Knowledge Discovery and Data Mining 2013
DOI: 10.1145/2487575.2488213
|View full text |Cite
|
Sign up to set email alerts
|

Detecting insider threats in a real corporate database of computer usage activity

Abstract: This paper reports on methods and results of an applied research project by a team consisting of SAIC and four universities to develop, integrate, and evaluate new approaches to detect the weak signals characteristic of insider threats on organizations' information systems. Our system combines structural and semantic information from a real corporate database of monitored activity on their users' computers to detect independently developed red team inserts of malicious insider activities. We have developed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 24 publications
1
71
0
Order By: Relevance
“…Experiments and results included in this paper extend previously reported results ( [21], [24], [25]) to cover 16 months of data from September 2012 through February 2014. Testing on the additional eight months included a number of new Red Team (RT) scenarios, new detection algorithms, and improved versions of existing detectors.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…Experiments and results included in this paper extend previously reported results ( [21], [24], [25]) to cover 16 months of data from September 2012 through February 2014. Testing on the additional eight months included a number of new Red Team (RT) scenarios, new detection algorithms, and improved versions of existing detectors.…”
supporting
confidence: 55%
“…Relational features such as the email and text-message communication graphs are used to provide comparison groups in some detectors. Different approaches to feature normalization are incorporated into variants of the same detection models used in PRODIGAL [21].…”
Section: B Developing a Diverse Suite Of Detectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Senator et al [10] developed multiple algorithms for anomaly detection and demonstrated the feasibility of proposed methods for insider threat detection. Magklaras and Furnell [11] proposed a threat evaluation system based on profiles of user behaviors to estimate the level of threat.…”
Section: Related Workmentioning
confidence: 99%